The effective private elementary school principals of Dumaguete City as perceived by the teachers: Their profile - Lachica, Loreta C. (Animo Repository, 1985)
This study constructs a profile of the private elementary school principals of Dumaguete City perceived as effective by the teachers. This study made use of the descriptive-evaluative survey. The effective principals were identified from the responses of their respective teachers to the evaluation questionnaire. After the effective principals were identified, their individual profiles were looked into to determine common characteristics from which the profile of the effective private elementary school principals of Dumaguete City was established. The respondents of the study were seven (7) private elementary school principals and ninety seven (97) teachers. Two instruments were used in this study: the questionnaire on profile of the private elementary school principals was adopted from the questionnaire by Pharis and Zakariya (1978) and the PAASCU Evaluation Questionnaire on the area of Administration and School Staff, particularly the items referring to the principal and administrative assistants, their preparation, qualification, duties and functions. Based on the findings of the study it was concluded that, experience as a professional in education, as a classroom teacher, as an assistant principal and on-the-job experience contributed greatly to principal effectiveness. More time spent at school and on school-related activities brought about principal effectiveness. This effectiveness was fostered when the principal was given authority in the selection of teachers. It was found that the superior's commendation enhances the principal's effectiveness. Also, a more positive outlook towards children's learning and general behavior led to principal effectiveness.